2015
DOI: 10.1002/2327-6924.12218
|View full text |Cite
|
Sign up to set email alerts
|

Articulating nurse practitioner practice using King's theory of goal attainment

Abstract: Purpose To further understand the interactions between nurse practitioners (NPs) and patients, King's nursing theory of goal attainment was applied as the conceptual framework to describe the interactions between NPs and patients in the primary care setting. Data sources Six dyads of NPs and their patients were video‐ and audio‐taped over three consecutive clinic visits. For the purposes of this arm of the study, the audio‐taped interactions were transcribed and then coded using King's concepts in her theory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Imogene King's descriptive study on nurse-patient interaction laid the foundation for concrete elements required for successful communication and transaction in the nurse practitioner-patient setting (33). Previous studies have demonstrated and validated King's transaction process using empirical data (30,34). These studies were conducted with nurses and in the pharmaceutical context, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Imogene King's descriptive study on nurse-patient interaction laid the foundation for concrete elements required for successful communication and transaction in the nurse practitioner-patient setting (33). Previous studies have demonstrated and validated King's transaction process using empirical data (30,34). These studies were conducted with nurses and in the pharmaceutical context, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In an exemplar of King's theory of goal attainment practiced in a clinical context, six dyads of nurse practitioners and their patients were video-taped over three consecutive clinic visits, and these visits were coded using King's concepts of goal attainment (Leon-Demare, MacDonald, Gregory, Katz, & Halas, 2015). The researchers reported that staff members recognized disturbances and embraced opportunities for goal setting to improve the health status of individuals.…”
Section: Theoretical Nursing Knowledgementioning
confidence: 99%
“…In this regard, the theory represents respect for patients and has a strong emphasis on information exchange, goal-setting, and patient-centered treatment. Therefore, applying King's goal attainment theory in nursing settings is expected to strengthen the foundation of nursing [14].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…The examination of recent studies in Korea and overseas has indicated that the goal attainment theory has been reflected in researches on the relationship between patients and nurses [12], nursing practice [14], nursing role [15], mentoring tools for nursing educators [16], telenursing practice [17], and nursing interventions [18,19].…”
Section: Introduction 1backgroundmentioning
confidence: 99%